Giant strides - VBO International (Yaba, Lagos [Nigeria] : VBO International, 1987)
Takes stock of the achievements, failures as well as constraints of the military administration in power.
In Nigeria there are so many opportunities for profitable investments and the welcome mat is out for genuine investors.
oif 10/05/17
Ref.
Keywords: Economic history; Politics and government; Social policy; Nigeria